Interactive footsteps sounds modulate the sense of effort without affecting the kinematics and metabolic parameters during treadmill-walking. (1st January 2018) - Turchet, Luca; Camponogara, Ivan; Nardello, Francesca; Zamparo, Paola; Cesari, Paola
Abstract: Previous research has shown that walkers provided with interactive simulations of footstep sounds on a surface material different from the one they are walking upon, experience pseudo-haptic illusions and adjust their walking kinematic according to the perceived surfaces' compliance. Since walking on real grounds with different degrees of compliance leads to different metabolic costs, an open question is whether pseudo-haptic illusions created by interactive footstep sounds are able to affect the metabolic parameters. This study investigated whether metabolic cost and movement's kinematics are affected by such interactive auditory feedback in a constrained condition as walking on a treadmill. Participants were walking on a treadmill under three listening conditions: actual footsteps sounds, interactive simulations of footstep sounds on gravel and snow. The metabolic and kinematic data, as well as the perceived exertion, sense of effort, easiness, and feeling of sinking were recorded. Results showed that interactive footstep sounds provided during treadmill walking did not affect kinematic and metabolic parameters of walking, while they were effective in modulating participants' perception. These results suggest that in a constrained and non self-selected pattern of locomotion the sound of action, even though correctly perceived, is not strong enough to induce a change in the metabolic and kinematics of the locomotion.